2020
DOI: 10.1021/acs.chemrev.0c00552
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Gold(III) Chemistry: Structure, Bonding, Reactivity, and Role in Homogeneous Catalysis

Abstract: Over the last decade the organometallic chemistry of gold(III) has seen remarkable advances. This includes the synthesis of the first examples of several compound classes that have long been hypothesized as being part of catalytic cycles, such as gold(III) alkene, alkyne, CO and hydride complexes, and important catalysis-relevant reaction steps have at last been demonstrated for gold, such as migratory insertion and β-H elimination reactions. Also, reaction pathways that were already known, such as the generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(165 citation statements)
references
References 595 publications
(1,252 reference statements)
3
144
0
Order By: Relevance
“…[279] Davies and Albrecht showed that sulphoxide tethered enynes 303 in presence of dichloro(2-pyridinecarboxylato)gold (III) or PtCl 2 undergoes a domino rearrangement to form dihydrothiophenones and dihydrothiopyranones 304 (Scheme 68). The overall process proceeds through Au(III)activated 5-exo-dig selective nucleophilic attack at the internal carbon of alkyne to form α-carbonyl metal carbenoid as key intermediate which leads to allyl sulphonium ylide to complete a [2,3]-sigmatropic rearrangement. [280] Compared to other sulphoxide rearrangement, this chemistry avoids the use of any sacrificial functional groups to grant access to sulphur ylides via operation of an internal redox process.…”
Section: Alkynyl Sulphoxide Rearrangementsmentioning
confidence: 99%
“…[279] Davies and Albrecht showed that sulphoxide tethered enynes 303 in presence of dichloro(2-pyridinecarboxylato)gold (III) or PtCl 2 undergoes a domino rearrangement to form dihydrothiophenones and dihydrothiopyranones 304 (Scheme 68). The overall process proceeds through Au(III)activated 5-exo-dig selective nucleophilic attack at the internal carbon of alkyne to form α-carbonyl metal carbenoid as key intermediate which leads to allyl sulphonium ylide to complete a [2,3]-sigmatropic rearrangement. [280] Compared to other sulphoxide rearrangement, this chemistry avoids the use of any sacrificial functional groups to grant access to sulphur ylides via operation of an internal redox process.…”
Section: Alkynyl Sulphoxide Rearrangementsmentioning
confidence: 99%
“…Likely, Au‐b is more stable and more reactive in phosphate buffer solution (pH 7.4) than Au‐c because the N‐heterocyclic carbene ligand in Au‐b has a stronger metal‐carbon σ bond, which provides enhanced stability and higher activities [23] . By contrast, Au‐c complexes possess high redox potential, leading to facile reduction of Au III complexes to metallic Au 0 species in the presence of electron‐rich reagents [24] . Overall, the Au‐b catalyst is a more suitable trigger for the gold‐mediated reaction for synthesis of 5‐methyl phenanthridinium derivatives in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the electron‐rich tertiary phosphine and amine ligands are not suitable for gold(III) ion because of the possible reduction. Electron‐deficient nitrogen‐containing ligands such as pyridines, Schiff bases, N‐heterocyclic carbenes and triazole derivatives, were adopted for stable gold(III) complexes [1x–z] . On the other hand, too stable gold(III) complexes tend to exhibit poor catalytic activity.…”
Section: Introductionmentioning
confidence: 99%